2011
DOI: 10.1021/om2006744
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrinuclear Complexes with Palladium, Rhodium, and Iridium Ions Assembled by Conformational Switching of a Tetraphosphine Ligand around a Palladium Center

Abstract: Reaction of [PdCl 2 (cod)] with a tetraphosphine, meso-bis[((diphenylphosphino)methyl)phenylphosphino]methane (dpmppm), afforded the mononuclear Pd II complexes [PdCl(dpmppm-κ 3 )]X (X = Cl (1a), PF 6 (1b)); the pincer-type dpmppm ligand coordinates to the Pd atom with two outer and one inner phosphorus atom to form fused six-and four-membered chelate rings. The remaining inner phosphine is uncoordinated and readily reacts with [Cp*MCl 2 ] 2 to give the heterodimetallic complexes [PdCl-(Cp*MCl 2 )(μ-dpmppm-κ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In contrast to the higher nuclearity systems, dpmppm also provides a scaffold for a hydride‐bridged dicopper(I) center, [Cu 2 (μ‐H)(μ‐ meso ‐dpmppm) 2 ]X (X=BF 4 , PF 6 ), which undergoes insertion of CO 2 under mild conditions to yield a formate‐bridged dicopper complex, [Cu 2 (μ‐HCO 2 )(μ‐ meso ‐dpmppm) 2 ]X . The versatile coordination behavior of meso ‐dpmppm further organized stepwise assemblies of heterotrinuclear metal ions of PdMM′ systems (M, M′=Rh, Ir) . These recent results from our group clearly suggested that the linear polyphosphines are potentially useful to create diverse multinuclear metal arrays.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the higher nuclearity systems, dpmppm also provides a scaffold for a hydride‐bridged dicopper(I) center, [Cu 2 (μ‐H)(μ‐ meso ‐dpmppm) 2 ]X (X=BF 4 , PF 6 ), which undergoes insertion of CO 2 under mild conditions to yield a formate‐bridged dicopper complex, [Cu 2 (μ‐HCO 2 )(μ‐ meso ‐dpmppm) 2 ]X . The versatile coordination behavior of meso ‐dpmppm further organized stepwise assemblies of heterotrinuclear metal ions of PdMM′ systems (M, M′=Rh, Ir) . These recent results from our group clearly suggested that the linear polyphosphines are potentially useful to create diverse multinuclear metal arrays.…”
Section: Methodsmentioning
confidence: 99%
“…Multinuclear transition‐metal complexes have extensively been studied to explore new aspects of functional materials because a variety of synergistic effects in multimetallic centers are expected to play key roles in developing catalytic systems, electronic, optical, and magnetic devices, and biomimetic functional molecules . To create desired multinuclear centers, design of multidentate metal supporting ligands is very important issue, and in this regard, we have prepared a methylene‐bridged linear tetraphosphane, meso ‐ and rac ‐bis[(diphenylphosphinomethyl)phenylphosphino]methane (dpmppm), and demonstrated that it effectively stabilized versatile tetra‐, tri‐, and dinuclear homo and heterometallic systems as well as mononuclear centers (Scheme ) . First of all, meso ‐ and rac ‐dpmppm preferably supported linearly ordered tetranuclear metal centers in κ 1 ,κ 1 ,κ 1 ,κ 1 coordination mode (Scheme a, Scheme f), exemplified by the linear octapalladium rigid‐rods, [Pd 8 ( meso ‐ or rac ‐dpmppm) 4 L 2 ] 4+ (L = none, MeCN, N , N ‐dimethylformamide (dmf), and isocyanides),, which dissociate at higher temperature T > 100 °C into two tetrapalladium units of {Pd 4 ( meso ‐ or rac ‐dpmppm) 2 } 2+ and interestingly they are self‐aligned at lower temperature T < 60 °C to restore the original rods through asymmetric recognition between the tetrapalladium units .…”
Section: Introductionmentioning
confidence: 99%
“…The meso ‐dpmppm ligand was found to surround a Pd II or Pt II mononuclear center in a pincer‐type κ 3 ‐fashion (Scheme e) affording [MCl(dpmppm‐κ 3 )] + (M = Pt, Pd) that involve fused six‐ and four‐membered chelate rings with an uncoordinated phosphane unit in the six‐membered ring, and are transformed, by addition of Cp*MCl 2 fragment (M = Rh, Ir) onto the uncoordinated phosphane, into [MCl(Cp*M′Cl 2 )(µ‐ meso ‐dpmppm‐κ 3 ,κ 1 )] + (M = Pt, Pd; M′ = Rh, Ir) (Scheme d) , . The PdM′ complex with meso ‐dpmppm‐κ 3 ,κ 1 bridge captured the third metal ion via cleavage of the four‐membered chelate ring to afford heterotrimetallic complexes, [PdCl 2 (Cp*M′Cl 2 )(Cp*MCl 2 )(µ‐ meso ‐dpmppm‐κ 2 ,κ 1 ,κ 1 )] and [PdCl(µ‐Cl)(Cp*M′Cl)(Cp*MCl 2 )(µ‐dpmppm‐κ 2 ,κ 1 ,κ 1 )]PF 6 (M, M′ = Rh, Ir), in stepwise ways (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexible coordination behavior of mesodpmppm further organized stepwise assemblies of heterotrinuclear metal ions of [PdCl 2 (Cp*M 0 Cl 2 )(Cp*MCl 2 )(m-dpmppmk 2 ,k 1 ,k 1 )] and [PdCl(m-Cl)(Cp*M 0 Cl)(Cp*MCl 2 )(m-dpmppm-k 2 ,k 1 ,k 1 )] þ (M, M 0 ¼ Rh, Ir, Cp* ¼ h 5 -pentamethylcyclopentadienyl) [38]. In addition, we have recently been successful in establishing lowvalent octapalladium chains supported by meso-dpmppm, as a coordinatively unsaturated Pd 8 rod, [Pd 8 (m-dpmppm) 4 ](BF 4 ) 4 , and the terminal-capped [Pd 8 (m-dpmppm) 4 (L) 2 ](BF 4 ) 4 (L ¼ 2,6-xylyl isocyanide (XylNC), CH 3 CN, N,N-dimethylformamide (dmf)) [39,40].…”
Section: Introductionmentioning
confidence: 99%